Energy-efficient routing protocol in wireless sensor networks based on bacterial foraging optimization - Abdulmalik Adil Abdulzahra; Baida’a Abdul Qader Khudor; Imad S. Alshawi (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Reserve the wireless sensor networks (WSNs) lifetime for as long as possible is a current goal. In WSNs, sensors are often limited in power. However, uneven power consumption (UPC) reduces lifetime, and its deterioration is considered one of the most critical problems. Therefore, balancing the energy consumption is a significant issue in the WSN, necessitating a routing protocol that is energy-efficient that extends the life of the network. A few protocols have been used to balance energy use across network nodes. This paper proposed a routing protocol energy-saving called Bacterial foraging optimization routing protocol (BFORP). BFORP attempts to investigate the problem of the life of WSNs. It can decrease the routing of excessive messages that may result in severe energy waste by recycling the information that frequents the source node into the sink. In the proposed method, the preferable node in the sending routes may be chosen by prioritizing the lowest traffic load, the highest residual energy, and the shortest path to the sink. In comparison to the known protocols used in routing, the results of the simulation have proven the efficacy of the suggested protocol in lowering energy employment and reducing the delay of end-to-end.